BRAF V600 Mutation and BRAF Kinase Inhibitors in Conjunction With Stereotactic Radiosurgery for Intracranial Melanoma Metastases: A Multicenter Retrospective Study. Issue 4 (29th May 2018) - Mastorakos, Panagiotis; Xu, Zhiyuan; Yu, James; Hess, Judith; Qian, Jack; Chatrath, Ajay; Taylor, Davis G; Kondziolka, Douglas; Warnick, Ronald; Chiang, Veronica; Sheehan, Jason
Abstract: BACKGROUND: The BRAF mutation has been identified as a potent target for the treatment of metastatic melanoma and BRAF inhibitors (BRAFi) have demonstrated promising results against melanoma brain metastases (BM). OBJECTIVE: To further investigate the effectiveness of this combined treatment regimen. METHODS: In this multicenter retrospective cohort study, 198 patients with known BRAF mutation status and treated with stereotactic radiosurgery (SRS) between 2011 and 2015 were identified. Kaplan–Meier methodology and multivariate regression analysis was then used to compare survival based on each parameter. RESULTS: The median survival after the diagnosis of BM in patients with BRAF mutation who received BRAFi was increased compared to survival in patients with wild-type BRAF (BRAF wt). In multivariate analysis, the BRAF mutation was an independent, positive prognostic factor with a hazard ratio of 0.59. BRAF mutated Patients who received BRAFi following SRS had improved survival compared to patients who received it before ( P  < .001) or concurrently ( P  = .007). PD-1 inhibitors improved survival, with more pronounced effect in patients not carrying the BRAF mutation. Among the patients who were treated with BRAFi, 10.4% developed intracerebral hematoma (ICH), in comparison to 3% of patients who were not treated with BRAFi ( P  = .03). CONCLUSION: In the setting of widespread use of BRAFi, the presence of a BRAF mutation is an independent predictor of better prognosis in patients with melanoma BM that underwent SRS. The effect of BRAFi is optimal when treatment is initiated at least 1 wk following SRS. BRAFi may increase the frequency of asymptomatic ICH.